The Influence of Democratic Parenting Style on Student Learning Outcomes at a Vocational High School - Ramadhani, Helfa Sri; Yanto, Yanto; Kusaini, Utami Niki (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2026)
This study is grounded in the important role of family, particularly democratic parenting characterized by open communication, warmth, and guided autonomy, in supporting students’ academic achievement. Differences in learning attitudes and behaviors among tenth-grade students during the transition from junior to vocational high school highlight the need to examine this relationship. This study aims to determine the influence of democratic parenting style on student learning outcomes in a state vocational high school. This research employed a quantitative, ex post facto design, involving a population of 699 students and a sample of 87 selected via simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed using descriptive statistics, percentage analysis, normality and linearity tests, and simple linear regression. The results show that democratic parenting is in the high category (76.33%), while student learning outcomes are in the good category (70.09%). The correlation coefficient (R) of 0.631 and R Square of 0.398 indicate that democratic parenting contributes 39.8% to student learning outcomes, demonstrating a significant positive influence. It is recommended that future research expand the study by including additional variables that may affect learning outcomes.